SUFI HEALING: Terapi dalam Literatur Tasawuf - Syukur, M. Amin (IAIN Walisongo Semarang, 2012)
Abstract Â This study reveals the Sufi healing, a therapy in the literature of Sufism. This study focuses on behaviors associated with the Sufi healing or prevention of disease, both physically and mentally, and then determines the aspects that support a system of rational and empirical therapy. The result achieved through this research is the discovery of an alternative treatment or prevention of appropriate disease in accordance with the tendency of society in the current era, the digital age. After investigation, it is revealed that Sufi healing is a form of alternative therapy that is done by taking the values of Sufism as a means of treatment or prevention. This model has been known in the community since Islam and Sufism itself evolved. Scientific references about the work system of medicine or healing in this manner, was found in a variety of transpersonal psychology theories, in which consciousness become one focus of the study. Medically, it is also known by the term psychoneurons-endocrine-immunology, where the conclusion states that there is a relationship between mind and body in the health problems for everyone. In other word, the mind influences health. Â *** Kajian ini mengungkap tentang sufi healing, yaitu terapi di dalam literatur tentang sifisme. Kajian ini memfokuskan pada perilaku yang berasosiasi dengan sufi healing atau pencegahan penyakit, baik secara fisik maupun mental, dan kemudian menentukan aspek-aspek yang mendukung sistem terapi rasional dan empirik. Hasil yang diperoleh dari kajian ini adalah penemuan treatment alternative atau preventif terhadap penyakit secara tepat yang sesuai dengan tuntutan masyarakat saat ini. Ditemukan bahwa sufi healing merupakan bentuk terapi alternatif yang dilakukan dengan menggunakan nilai-nilai sufisme sebagai cara treatment atau pencegahan. Model ini telah dikenal dalam masyarakat sejak Islam dan sufisme berkembang. Rujukan ilmiah dari mengenai sistem kerja pengobatannya dapat ditemukan dalam berbagai teori psikologi transpersonal, di mana kesadaran menjadi fokus kajian. Secara medis, pengobatan ini juga disebut psycho-neurons-endocrine-immunology, yang kesimpulannya adalah adanya hubungan antara fikiran dan tubuh dalam kesehatan manusia, Â Keywords: sufi, sufisme, sufi healing, transpersonal, psikologi